The association between serum sex steroid hormone concentrations and intraprostatic inflammation in men without prostate cancer and irrespective of clinical indication for biopsy in the placebo arm of the Prostate Cancer Prevention Trial. Issue 11 (7th June 2020) - Chadid, Susan; Barber, John R.; Nelson, William G.; Gurel, Bora; Lucia, M. Scott; Thompson, Ian M.; Goodman, Phyllis J.; Stanczyk, Frank Z.; Parnes, Howard L.; Lippman, Scott M.; De Marzo, Angelo M.; Platz, Elizabeth A.
Abstract: Background: Intraprostatic inflammation is an emerging prostate cancer risk factor. Estrogens are pro‐inflammatory while androgens are anti‐inflammatory. Thus, we investigated whether serum sex steroid hormone concentrations are associated with intraprostatic inflammation to inform mechanistic links among hormones, inflammation, and prostate cancer. Methods: We conducted a cross‐sectional study among 247 men in the placebo arm of the Prostate Cancer Prevention Trial who had a negative end‐of‐study biopsy, most (92.7%) performed without clinical indication per trial protocol. Serum estradiol, estrone, and testosterone were previously measured by immunoassay in pooled baseline and Year 3 serum. Free estradiol and free testosterone were calculated. Inflammation was visually assessed (median of three prostate biopsy cores per man). Polytomous or logistic regression was used to estimate the odds ratio (OR) and 95% confidence interval (CI) of some or all cores inflamed (both vs none) or any core inflamed (vs none) by hormone tertile, adjusting for age, race, and family history. We evaluated effect modification by waist circumference and body mass index (BMI). Results: In all, 51.4% had some and 26.3% had all cores inflamed. Free ( P ‐trend = .11) but not total estradiol was suggestively inversely associated with all cores inflamed. In men with waist circumference greater than or equal to 102 cm ( P ‐trend = .021) and BMI ≥ 27.09 kg/m 2 ( P ‐trend = .0037) free estradiol was inversely associated with any core inflamed. Estrone was inversely associated with all cores inflamed (T3: OR = 0.36, 95% CI 0.14‐0.95, P ‐trend = .036). Total (T3: OR = 1.91, 95% CI 0.91‐4.02, P ‐trend = .11) and free (T3: OR = 2.19, 95% CI 1.01‐4.74, P ‐trend = .05) testosterone were positively associated with any core inflamed, especially free testosterone in men with waist circumference less than 102 cm (T3: OR = 3.51, 95% CI 1.03‐12.11, P ‐trend = .05). Conclusions: In this first study in men without prostate cancer and irrespective of clinical indication for biopsy, contrary to the hypothesis, circulating estrogens appeared to be inversely associated, especially in heavy men, whereas androgens appeared to be positively associated with intraprostatic inflammation.